Spinal cord: Regional anatomy, cytoarchitecture and chemoarchitecture - Sengul, G.; Watson, Charles (Academic Press, Elsevier, 2012)
The spinal cord is composed of gray matter and white matter. The white matter is composed mostly of longitudinally running axons and also glial cells. The gray matter is composed of nine distinct cellular layers, or laminae, organized from dorsal to ventral, with the remaining area (area 10) surrounding the central canal. This lamination pattern was first defined by Rexed (1952, 1954) in the cat. Each lamina possesses different physiological, histochemical, and cytoarchitectonic characteristics. Laminae 1-6 constitute the dorsal horn, lamina 7 is the intermediate gray matter, laminae 8 and 9 constitute the ventral horn, and area 10 corresponds to the area around the central canal. There are also several named cell groups (nuclei) within the spinal cord. Most of these are located within the numbered gray laminae of the spinal cord. These are the dorsal nucleus (Clarke's column), the internal basilar nucleus, the central cervical nucleus, the intermediolateral cell column, the intermediomedial nucleus, the lumbar and dorsal commissural nuclei, the sacral precerebellar nucleus, and the sacral parasympathetic nucleus. There are also two significant neuronal groups in the white matter of the lateral columns of the spinal cord, the lateral cervical and lateral spinal nuclei.